THE IMPLICIT CHARACTER OF INFORMATION MEDIATION - Santos Neto, Joao Arlindo dos [UNESP]; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Campina Grande, 2017)
Discusses the implicit character of information mediation within the work environment of the librarian, based on theoretical basis and analysis of speech of professionals who work in a university library. Addresses the conceptual aspects of the term information mediation from different perspectives, but mainly from the perspective of the research of Information Science and presents possibilities of mediation implied, emphasizing the interference carried out by the information professional. Possesses theoretical character, qualitative approach, exploratory nature and about the method is characterized as bibliographical and field research. As results presents the panorama of implicit mediation, the social dimensions, ethical and informational present in this mediation and that are based on the librarian doings. Concludes that the implicit information mediation is little remembered and discussed in investigations of the area, while the explicit mediation is more investigated and debated.
Keywords: Information mediation; Implicit mediation; Interference of the librarian; Discourse analysis